Production, Purification and Partial Characterization of Four Lipases from a Thermophile Isolated from Deception Island - Blamey-Alegria, J (2013)
Four lipases were purified from ID17, a thermophilic bacterium belonging to Geobacillus genus isolated from Deception Island, Antarctica. Lipase activity was detected by opacity test and p-nitrophenyl laurate methods. Lipase production was better in a medium containing tryptone as the carbon and nitrogen source, without non-ionic detergents and pH 7.5. Proteins were ultrafiltered from supernatant and separated using anion exchange and size exclusion chromatography resulting in four distinct fractions with lipase activity (called Lip1-4). Purified lipases showed an optimal pH at 9.0, 9.5, 10.0 and 8.0 and temperature at 65, 70, 75 and 80 C for Lip1-4, respectively. Lip1 and Lip2 showed higher activity using p-nitrophenol decanoate as substrate, whereas Lip3 and Lip4 prefer p-nitrophenol laurate. Based on their molecular weight Lip1 and Lip2 are trimeric and pentameric proteins, respectively, whereas Lip3 and Lip4 are monomeric proteins. Lip1 was exceptionally thermostable maintaining 70 % of its activity after incubating it at 70 C for 8 h. Based on their characteristics, the four lipases obtained from ID17 are good candidates to understand the mechanisms of lipase stability and to be used in different types of industrial applications. © 2013 AOCS.